Integration of Three Vehicle Fleet Types for Delivering Relief Supplies During a Natural Disaster - Kitjacharoenchai, Patchara; Sittivijan, Peerapol (Applied Science and Engineering Progress, 2023)
The combined use of trucks and drones in last-mile delivery offers a more efficient and faster way to make deliveries from an operational standpoint. In this paper, we propose a new routing model that combines different vehicle fleets, including hybrid trucks, traditional trucks, and large drones, to deliver packages from a depot to different destinations cooperatively. This research will give us a better understanding of this drone logistics application, particularly in routing optimization. It can be further implemented to mitigate the impacts of natural disasters, mainly earthquakes, flooding, and landslides. This research aims to study the possibility of using drones to deliver relief supplies such as food, water, and medicine for humanitarian purposes during natural disaster periods to find the best possible route to directly reach the destination and minimize the flying time in the air. We develop a Mixed Integer Programming (MIP) formulation to solve the I-VRPD optimally on a simulated small-scale problem and conduct a case study in one of the most affected regions by natural disasters. The numerical analysis demonstrates an improvement in the delivery time using three experiments that include testing the model on a set of benchmark problems and a case study based on the real scenario. The results show that the delivery time of the proposed model with the integration of three types of vehicle fleets can outperform the operation performed by a single-vehicle fleet by a significant percentage.